Strategy of Cattle Development to Increase Farmers' Income - Najeriyah, Najeriyah; Abidin, Zaenal; Wulandari, Triyana (CV. Zabags Qu Publish, 2025)
This research aims to identify Cattle Livestock Development Strategies to Increase Farmer Income. The data analysis method used in this research is descriptive analysis or qualitative descriptive. Participants in this research are breeders. In obtaining data in the field, observation, interviews and documentation are used. The research results obtained are: Based on the data analysis in this research, the researcher can conclude that there are several factors that influence the development of cattle in Pandan Jaya Village, namely Capital, Feed and Climate as well as Cattle Development Strategies to Increase Farmer Income, namely by collaborating with the government provides livestock assistance to breeders and also to independent breeders who implement a profit-sharing system.